2016
DOI: 10.1159/000455948
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of apoM Polymorphism Associated with HDL Metabolism on Obese Korean Adults

Abstract: Background: Apolipoprotein M (apoM) is a recently identified apolipoprotein associated with high-density lipoprotein (HDL) in coronary artery disease (CAD), but the association between apoM polymorphism and obesity has not been reported. Aim: To investigate the association between apoM polymorphism and obesity prevalence in 584 Korean adults. Methods: A total of 584 individuals aged between 30 and 80 years were recruited from Yonsei Medical Center in Seoul, Korea, and divided into obese (OB; body mass index, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Therefore, ApoM might play an essential role in HDL metabolism [ 1 ]. Some other studies also proved that ApoM polymorphism was associated with HDL metabolism in obese patients [ 2 ]. Our study showed a significant decline in plasmatic ApoM and HDL-C levels in obese patients, and the plasmatic ApoM level was positively correlated with HDL-C level, which might indicate that, as an important apolipoprotein of HDL, the decreased level of ApoM due to its abnormal metabolism, might contribute in the decreased level of HDL-C in obese patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, ApoM might play an essential role in HDL metabolism [ 1 ]. Some other studies also proved that ApoM polymorphism was associated with HDL metabolism in obese patients [ 2 ]. Our study showed a significant decline in plasmatic ApoM and HDL-C levels in obese patients, and the plasmatic ApoM level was positively correlated with HDL-C level, which might indicate that, as an important apolipoprotein of HDL, the decreased level of ApoM due to its abnormal metabolism, might contribute in the decreased level of HDL-C in obese patients.…”
Section: Discussionmentioning
confidence: 92%
“…High-density lipoprotein cholesterol (HDL-C) level is often detected as decreased in obese patients, but the mechanism is still unclear. Apolipoprotein M (ApoM), a newly identified apolipoprotein, has been reported to play an important role in the metabolism of HDL-C [ 1 , 2 ]. The ApoM gene is located in the MHC-III region of many inflammatory-related genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, apoM has been deemed an important component of rare adipokines associated with healthy metabolic status [ 18 ]. APOM gene polymorphism is also related to the metabolism of HDL in obese Korean male adults [ 20 ]. The aforementioned studies have shown that apoM may play a causative role in insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding apoM gene resides on chromosome 6 in the major histocompatibility complex class III region in humans and consists of a ~2 kb promoter sequence, 6 exons and 5 introns. To date, 5 SNPs in the apoM promoter region and 2 SNPs in the open reading frame (intron 5) are reported and associated with an altered lipid profile and various diseases such as diabetes, rheumatoid arthritis or cardio vascular disease [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%